Global practices of meningococcal vaccine use and impact on invasive disease. (January 2014) - Ali, Asad; Jafri, Rabab Zehra; Messonnier, Nancy; Tevi-Benissan, Carol; Durrheim, David; Eskola, Juhani; Fermon, Florence; Klugman, Keith P.; Ramsay, Mary; Sow, Samba; Zhujun, Shao; Bhutta, Zulfiqar; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> A number of countries now include meningococcal vaccines in their routine immunization programs. This review focuses on different approaches to including meningococcal vaccines in country programs across the world and their effect on the burden of invasive meningococcal disease (IMD) as reflected by pre and post-vaccine incidence rates in the last 20 years. Mass campaigns using conjugated meningococcal vaccines have lead to control of serogroup C meningococcal disease in the UK, Canada, Australia, Spain, Belgium, Ireland, and Iceland. Serogroup B disease, predominant in New Zealand, has been dramatically decreased, partly due to the introduction of an outer membrane vesicle (OMV) vaccine. Polysaccharide vaccines were used in high risk people in Saudi Arabia and Syria and in routine immunization in China and Egypt. The highest incidence region of the meningitis belt initiated vaccination with the serogroup A conjugate vaccine in 2010 and catch-up vaccination is ongoing. Overall results of this vaccine introduction are encouraging especially in countries with a moderate to high level of endemic disease. Continued surveillance is required to monitor effectiveness in countries that recently implemented these programs.